In-Vitro Antibiogram Screening of Citrullus lanatus (Watermelon) Seeds and Peels against Some Food Spoilage Bacterial Isolates - Rabiu, A.A.; Kabir, A.; Usman, M.T.; Abdulaziz, D. (International Journal of Scientific Research in Biological Sciences, 2023)
Citrullus lanatus (watermelon) is a fruits consumed all over the world and it comprised of four part; Seed, Pulp/Fleshy, Rind and Peel. Its Peels and Seeds are usually discarded as waste. This study aimed at determining the in-vitro antibiogram screening of Citrullus lanatus seeds and peels some food spoilage bacterial isolate using three varieties of watermelon; Sugar Baby, Odell’s white and Sakata Seed and Peels, the Seeds and Peels were dried and phytochemical constituent extracted by aqueous solvent. The extracts were subjected to antimicrobial assay using agar well diffusion against some food spoilage bacterial isolates (Staphylococcus aureus and Escherichia coli). The MIC and MBC was determined according to standard protocols. Phytochemical analysis revealed the presence of Alkaloid, Flavalonoid, Tannins and Reducing Sugar. Results of Antimicrobial Assay revealed that S.aureus and E.coli were susceptible to the extracts, with E.coli and S.aureus having 17mm and 15mm zone of inhibitionas the highest at concentration of 200mg/ml and 200mg/ml respectively. MIC and MBC results for E.coli and S. aureus were in closed range of 80mg/ml -100mg/ml respectively. The finding of this study showed that aqueous extracts of Seeds and Peels of C. lanatus contained bioactive compounds with potent antibacterial activity.